THINKING OF ISLAMIC EDUCATION IN THE GOLDEN TIME OF ISLAM - mulia mulia (Jurnal Teknologi Pendidikan Madrasah, 2022)
Islamic history records that the Abbasid period was the "golden age" of Islam, especially during the reign of Harun al-Rashid and al-Makmum, because of the intellectual sciences such as philosophy, geometry, mathematics, astronomy, chemistry, history, and geography. At this time has begun to enter and emerge, the development of educational institutions, as well as the birth of great educational ideas. It is not surprising that at this time there were prominent ulama (imam) such as Imam Abu Hanifah (80-150 H), Imam Malik (95-179 H), Imam Shafi'i (150-204), Imam Ahmad bin Hambal (164-241 H). H), known as Aimmatu mazahib al-Arba'ah (four priests of the fiqh school) which is still followed by Muslims around the world